Efforts To Improve The Mathematical Logic Intelligence Of Children Aged 5-6 Years Through Loose Part Media At Paud Harapan Ummat, Sari Rejo Village, Medan Polonia District - Dewi, Sri Kesuma; Parapat, Asmidar (Yayasan Multidimensi Kreatif, 2025)
This study aims to find out how to improve the mathematical logic intelligence of children aged 5-6 years through loose part media at PAUD Harapan Ummat, Sari Rejo Village, Medan Polonia District. To support the ability of mathematical logic intelligence in early childhood 5-6 years old, it can be done by utilizing loose part media, which includes natural materials, such as leaves, seeds, grains and shells. This study uses the Classroom Action Research method.The data collection techniques carried out are observation and documentation.with two cycles. Each cycle consists of 2 meetings. Then the researcher will observe the improvement of children's mathematical logic intelligence in each cycle to see the percentage increase. Observations were carried out based on research instruments in the form of BB, MB, BSH, BSB. Therefore, the conclusion of the study proves the effectiveness of loose part media in developing early childhood logic intelligence skills. Researchers recommend teachers to use loose part media to stimulate the mathematical logic intelligence of 5-6-year-old children.